Assessing the efficacy of 3D window double screens (3D-WDS) in reducing malaria transmission in northeastern Tanzania: Study protocol for a two-arm cluster-randomised controlled trial - William N. Kisinza; Subam Kathet; Victor Mwingira; Maija Meri; Frank S. Magogo; Veneranda M. Bwana; Hanna Granroth-Wilding; Pendael Machafuko; Patrick Tungu; Mikko Aalto; Tomi Hakala; Markku Honkala; et al. (Contemporary Clinical Trials Communications)
Background: The rise of insecticide resistance in malaria vectors has highlighted the urgent need for alternative vector control methods that do not rely on insecticides. The 3D-Screen, an innovative window screen featuring 3D conical structures integrated into a mesh, offers a promising solution. When installed as a double-screen setup (3D-Window Double Screen, or 3D-WDS) in window openings, its unidirectional design allows mosquitoes to enter the space between the screens from either the outside or inside of the living area, effectively trapping them within the enclosure. Previous laboratory and experimental hut studies have demonstrated the high efficacy of 3D-WDS in capturing host-seeking mosquitoes. This study aims to evaluate the epidemiological, entomological, and social impacts of implementing 3D-Screens in community settings. Methods/design: A two-arm, cluster-randomised controlled trial (cRCT) was conducted to assess whether houses equipped with both 3D-WDS and long-lasting insecticidal nets (LLINs) provide enhanced protection against malaria compared to LLINs alone. Twenty hamlets across 17 villages in Muheza, Tanzania, were evaluated for malaria prevalence, vector densities, entomological inoculation rates, and insecticide resistance levels. Fourteen hamlets with similar epidemiological and entomological profiles were then randomised: seven were assigned to the intervention group (3D-WDS + LLINs), and seven served as the control group (LLINs alone). Epidemiological and entomological surveillance were conducted at 10-week intervals over a 52-week follow-up period. Ancillary social science studies were conducted to assess community perceptions of the 3D-WDS intervention, focusing on acceptability and factors influencing its sustainability. Statistical analyses will use mixed-effects models to compare the impact of 3D-WDS combined with LLINs versus LLINs alone. Discussion: The 3D-WDS has the potential to reduce malaria transmission by providing a non-insecticidal, sustainable approach to mosquito control. Findings from this trial will demonstrate its real-world effectiveness and contribute to the development of scalable, long-term strategies for malaria prevention. Trial registration: ISRCTN Registry, ISRCTN87169034. Trial status: The study was initiated in June 2019, recruitment and sampling were completed in June 2021, sample analyses, and statistical evaluations are ongoing.